Postgraduate Studies As A Form of Lifelong Learning In The Offer of Polish Universities - Slawomir ZIOLKOWSKI; Michal BROZYNA (Communications of International Proceedings, 2025)
This study explores postgraduate studies as a key component of lifelong learning (LLL) within the context of Polish universities. It examines their historical development, legal frameworks, and alignment with international and European Union policies. Postgraduate studies are presented as an adaptive educational model responding to rapid technological progress, demographic changes, and evolving labor market demands. The paper highlights their role in enhancing professional qualifications, bridging gaps in formal education, and fostering social resilience. The historical analysis traces the evolution of adult education in Poland from the early 20th century to modern times, emphasizing milestones such as the introduction of formal postgraduate studies under the Higher Education Act of 1982. Legal provisions currently governing these programs are outlined, including their integration into Poland’s Qualifications Framework (PRK), which aligns with the European Qualifications Framework (EQF). Internationally, postgraduate studies are framed within broader LLL strategies endorsed by UNESCO, OECD, and EU initiatives like the Lisbon Strategy and Europe 2020. These policies underscore the importance of lifelong learning for global competitiveness and sustainable development. The study concludes that postgraduate studies could play a critical role in updating knowledge, promoting social integration, and supporting professional mobility, while identifying barriers to their full utilization within Poland’s education system.
Keywords: Postgraduate studies; human development; lifelong learning